Variation in safety culture dimensions within and between US and Swiss Hospital Units: an exploratory study. Issue 1 (6th July 2012) - Schwendimann, René; Zimmermann, Natalie; Küng, Kaspar; Ausserhofer, Dietmar; Sexton, Bryan
Abstract : Background: The purpose of this study was to explore the variability in safety culture dimensions within and between Swiss and US clinical areas. Methods: Cross-sectional design. The 30-item Safety Attitudes Questionnaire (SAQ) was distributed in 2009 to clinicians involved in direct patient care in medical and surgical units of two Swiss and 10 US hospitals. At the unit level, results were calculated as the percentage of respondents within a unit who reported positive perceptions. MANOVA and ANOVA were used to test for differences between and within US and Swiss hospital units. Results: In total, 1370 clinicians from 54 hospital units responded (response rate 84%), including 1273 nurses and 97 physicians. In Swiss hospital units, three SAQ dimensions were lower (safety climate, p=0.024; stress recognition, p<0.001; and perceptions of management, p<0.001) compared with US hospital units. There was significant variability in four out of six SAQ dimensions (teamwork climate, safety climate, job satisfaction and perceptions of unit management) (p<0.001). Moreover, intraclass correlations indicate that these four dimensions vary more at the unit level than hospital level, whereas stress recognition and working conditions vary more at the hospital level. Conclusions: The authors found differences in SAQ dimensions at the country, hospital and unit levels. The general emphases placed on teamwork and safety climate in quality and safety efforts appear to be highlighting dimensions that vary more at the unit than hospital level. They suggest that patient safety improvement interventions target unit level changes, and they support the emphasis being placed on teamwork and safety climate, as these vary significantly at the unit level across countries.